Radiotherapy benefits outweigh risks for breast cancer in modern era - Huang, Chih-Jen; Lee, Hsin-Hua (Translational Cancer Research; Vol 6, Supplement 6 (August 29, 2017): Translational Cancer Research, 2017)
The detrimental effects of smoking are well-known. Public health measures have focused on the prevention of tobacco use and cessation of its use. The prevalence of smoking was influenced not merely by social customs but tobacco control policies as well. Most men in many parts of Asia and central and Eastern Europe smoke (1). There are more women in Europe smoke than women in other regions. The male and female smoking prevalence have become virtually the same in some European countries (2). There is the highest prevalence of smoking among women in Western societies. It is about 40% in some European countries. The mortality rate of lung cancer continues to rise among continental European women (3).